Q460DE grade Z-direction performance hot-rolled H-beam and production method

By adopting low-carbon equivalent CEV and low Pcm component systems in heavy-duty hot-rolled H-shaped steel, combined with Nb/V microalloyation and rolling process optimization, the problem of poor welding performance of heavy-duty hot-rolled H-shaped steel is solved, and an efficient and low-carbon production process is achieved, and the weldability and production efficiency of the product is improved.

CN116516246BActive Publication Date: 2025-04-11МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310189236.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-04-11
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

The welding performance of existing heavy-duty hot-rolled H-shaped steel with a flange thickness of more than 50mm needs to be improved, and the production process cannot simply refer to the manufacturing process of steel plates.

Method used

A composition system with low carbon equivalent CEV and low welded crack sensitivity index Pcm was adopted, combined with Nb/V microalloyation and optimized rolling procedures and rolling rhythm, through fine crystal strengthening, solid solution strengthening and phase change strengthening, a 50-120mm thick Q460DE grade heavy-duty hot-rolled H-shaped steel was developed.

Benefits of technology

The weldability of heavy-duty hot-rolled H-shaped steel has been significantly improved, its usability has been improved, and hot-loading and hot-transfer have been achieved through optimizing the production process, which has improved production efficiency, saved energy consumption, and achieved low-carbon green production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516246B_ABST
    Figure CN116516246B_ABST
Patent Text Reader

Abstract

The invention discloses a Q460DE grade Z-direction performance hot-rolled H-beam and a production method, belonging to the technical field of steel. The carbon equivalent CEV of the H-beam is 0.36-0.41%, and the welding crack sensitivity index Pcm is 0.18-0.23%; the flange thickness is 50-120 mm, and at 1 / 6 of the flange width direction and 1 / 4 of the flange thickness direction: the size of the Nb (CN) second phase particle is less than 60 nm, the size of the V (CN) second phase particle is less than 30 nm, and the microstructure is ferrite and pearlite. The production method is: molten iron pretreatment → alloy baking → converter smelting → LF refining → continuous casting → hot charging → heating furnace heating → high-pressure water descaling → blanking machine rolling → universal machine rolling → cooling bed air cooling. The invention can obtain 50-120 mm thick Q460DE heavy hot-rolled H-beam with excellent welding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel, and in particular relates to a Q460DE grade Z-direction hot-rolled H-shaped steel with excellent weldability and a production method. Background Art

[0002] Hot-rolled H-beam is an economical and efficient hot-rolled profile with more optimized cross-sectional area distribution and more reasonable strength-to-weight ratio. Due to its advantages of strong bending resistance, simple construction, cost saving and light structure, hot-rolled H-beam has been widely used in high-rise buildings, large-span venues, marine engineering, bridge structures and other fields.

[0003] With the development of science and technology, the construction engineering structure has gradually become larger, and the hot-rolled H-beam has also been required to be larger. In order to meet the needs of large-scale engineering structure construction, advanced countries such as Japan, Luxembourg, the United States and the United Kingdom have successively developed heavy-duty hot-rolled H-beams. China also built and put into operation the first domestic heavy-duty hot-rolled H-beam production line with an annual output of 800,000 tons in mid-2019.

[0004] Since the large-scale hot-rolled H-beam will sharply deteriorate the high performance of the product, the technology related to easy-to-weld high-performance heavy-duty hot-rolled H-beam has yet to be developed. In addition, compared with steel plates, the cross-section of hot-rolled H-beam is complex, which limits the rolling conditions (rolling temperature, rolling compression ratio). Therefore, the production of hot-rolled H-beam cannot simply refer to the manufacturing process and chemical composition of steel plates to achieve its development.

[0005] After searching, the Chinese patent application number is 202210050093.3, and the application publication date is April 19, 2022. It discloses a high-performance, heavy hot-rolled H-beam with a yield strength of 460MPa and a production method thereof. The C-Si-Mn-V-Nb-Ni-Ti composition design idea is adopted. After molten iron pretreatment → converter smelting → argon blowing refining → LF refining → RH → full protection casting of special-shaped blanks → billet heating → rolling → QST cooling after rolling, the yield strength is above 460MPa, the tensile strength is ≥640MPa, the elongation is above 20%, the 0℃ longitudinal V-shaped impact energy KV2 average is above 70J, the web thickness direction performance and the flange thickness direction performance are above 45%, and the comprehensive mechanical properties are excellent. The flange thickness is 70-140mm, and the yield strength is 460MPa. High-performance, heavy hot-rolled H-beam. The composition and process adopted in this invention are different from those of the present invention, and the weldability of the produced product is poor.

[0006] The Chinese patent application number is 202011217422.6, and the application publication date is March 9, 2021. It discloses an ultra-thick hot-rolled H-beam and its production method, which adopts C, Si, Mn, Cr, Cu, Nb, V, Ti, Al, and N composition design, and adopts universal water spray cooling process before and after rolling to develop a flange thickness of 90mm to 150mm Q460MPa hot-rolled H-beam. This invention adopts a high-cost composition design of multiple alloys with weather resistance, and its composition and process are different from the present invention, and the product produced has poor weldability.

[0007] The Chinese patent application number is 202011243693.9, and the application publication date is February 26, 2021. It discloses a low-cost 460MPa grade hot-rolled H-beam with excellent low-temperature toughness and its production method, which is composed of C, Si, Mn, P, S, V, Ni, Cr, N, and the rest is Fe and unavoidable impurities. The content ratio of V to N is 8:1-10:1. Based on the actual production of hot-rolled H-beam, through reasonable component ratio and full-process TMCP technology, a 460MPa grade hot-rolled H-beam with a flange thickness of 30mm-50mm, high strength, high and low temperature toughness, excellent weldability and thickness direction performance is developed. This invention involves the thickness of the product and adopts a post-rolling water cooling process, which is essentially different from the present invention.

[0008] The Chinese patent application number is 202010893602.X, and the application publication date is December 4, 2020. It discloses a 460MPa yield strength low-temperature resistant hot-rolled H-beam and its preparation method, which contains C, Si, Mn, P, S, Nb, V, and the rest is Fe and unavoidable impurities, producing a 460MPa high-strength, high-temperature resistant heavy-duty hot-rolled H-beam with a flange thickness of more than 70mm. The process flow of this invention does not take into account the harmful effects of hydrogen in the steel on the performance of heavy-duty hot-rolled H-beam. At the same time, the nitrogen content in the steel is not controlled, which can easily cause product surface quality problems; in addition, the rolling temperature specified in the invention is relatively low, the deformation resistance of the rolled piece is large, and the rolling mill load is large, which can easily cause the rolling mill to over-current, which is not conducive to production.

[0009] According to the current survey, there has been no report on the development of Q460DE grade Z-direction performance with high efficiency, energy saving and green environmental protection through production process optimization, coupling micro-alloying composition control and rolling process control for heavy hot-rolled H-beam with flange thickness exceeding 50mm while ensuring good weldability. Summary of the invention

[0010] 1. Problems to be solved

[0011] In view of the problem that the welding performance of the existing heavy-duty hot-rolled H-shaped steel with a flange thickness exceeding 50 mm needs to be improved, the present invention provides a Q460DE grade Z-direction performance hot-rolled H-shaped steel and a production method. By designing a chemical composition system and optimizing the rolling procedure and rolling rhythm, 50-120 mm thick Q460DE heavy-duty hot-rolled H-shaped steel is developed by utilizing fine grain strengthening, solid solution strengthening and phase transformation strengthening. At the same time, the rolling process is optimized to achieve hot loading and hot delivery of products, thereby improving product production efficiency, saving product energy consumption, and realizing low-carbon green production.

[0012] 2. Technical solution

[0013] To solve the above problems, the present invention adopts the following technical solutions.

[0014] A Q460DE grade Z-direction performance hot-rolled H-beam, the carbon equivalent CEV of the H-beam is 0.36-0.41%, the welding crack sensitivity index Pcm is 0.18-0.23%, and the Q460DE heavy hot-rolled H-beam is designed with a component system of low carbon equivalent CEV and low welding crack sensitivity index Pcm, which improves its weldability and enhances its usability; the flange thickness is 50-120mm, at 1 / 6 of the flange width direction and 1 / 4 of the flange thickness direction (the hot-rolled H-beam mechanical properties sampling position specified in the national standard GB / T 2975-2018 standard, the organization and second phase particles at this position are representative): the size of the Nb (CN) second phase particles is less than 60nm, the size of the V (CN) second phase particles is less than 30nm, and the organization components are ferrite and pearlite. Among them, the calculation formulas of carbon equivalent CEV and welding crack sensitivity index Pcm are:

[0015] CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15;

[0016] Pcm=C+Si / 30+Mn / 20+Cu / 20+Ni / 60+Cr / 20+Mo / 15+V / 10+5B.

[0017] Carbon equivalent CEV and welding crack sensitivity index Pcm are important indexes for evaluating the weldability of steel. Carbon equivalent CEV and welding crack sensitivity index Pcm are inversely proportional to the weldability of steel. When CEV≤0.42% and Pcm≤0.24%, the steel has excellent weldability. Therefore, the upper limit of Pcm is set to 0.23 and the upper limit of CEV is set to 0.41%. Considering the performance requirements of steel, especially the strength requirements, the lower limit of Pcm is set to 0.18% and the lower limit of CEV is set to 0.36%.

[0018] Furthermore, at 1 / 6 of the flange width and 1 / 4 of the flange thickness: the volume fraction of Nb(CN) second phase particles with a size of 20-40 nm is 0.03-0.04%, and the volume fraction of V(CN) second phase particles with a size of 5-15 nm is 0.06-0.08%.

[0019] Furthermore, at 1 / 6 of the flange width and 1 / 4 of the flange thickness: the ferrite is less than 30 μm and accounts for 74-78% by volume, wherein the volume fraction of 6-12 μm ferrite accounts for 85% of the ferrite volume.

[0020] Furthermore, in the chemical composition system of the H-beam, the weight percentages of Nb and V w(Nb) and w(V) satisfy formula (a):

[0021] w(Nb)+ w(V)-0.079=0.050~0.070% (a);

[0022] The main purpose of adding Nb (niobium) and V (vanadium) alloys is to use the large amount of fine second-phase particles dispersed and precipitated by the two in the universal rolling stage to prevent austenite recrystallization and recrystallization grain growth, refine the austenite grains, and improve the strength and toughness of hot-rolled H-beams through grain refinement. In order to ensure that there are a large number of second-phase particles in the universal rolling stage, w(Nb)+w(V)-0.079 is set to 0.050~0.070%.

[0023] Further, in the chemical composition system of H-beam, the chemical composition and its weight percentage are: C: 0.04-0.12%; Si: 0.10-0.60%, Mn: 1.00-1.70%, P: ≤0.015%; S: ≤0.007%; Nb: 0.01-0.06%; V: 0.080-0.120%; N: 0.0040-0.0100%; H: ≤0.0002%, and the rest are Fe and unavoidable impurity elements. It is worth noting that the unavoidable impurity elements include trace amounts of Cr, Mo, Ni, Cu and B, which are brought in during the smelting of molten steel due to the small amount of ore or scrap steel. Since the introduction of these elements will affect the CEV and Pcm of the steel, and thus affect the weldability of the steel, the less these elements in this product, the better.

[0024] The C content is set to 0.04-0.12%. C (carbon) is an element that is effective in strengthening steel. Therefore, the lower limit of the C content is set to 0.04%. On the other hand, when the C content is greater than 0.12%, the carbon equivalent CEV and welding crack sensitivity index Pcm of the H-beam will be significantly increased, the weldability of the H-beam will be reduced, and at the same time, the low temperature toughness of the H-beam will be significantly reduced. Therefore, the upper limit of the C content is set to 0.12%.

[0025] The Si content is set to 0.10-0.60%. Si (silicon) is a deoxidizing element and also an element that helps to improve strength. Therefore, the lower limit of the Si content is set to 0.10%. On the other hand, if the Si content is greater than 0.60%, it will accelerate high-temperature delamination, deteriorate toughness and lamellar tearing performance, and also have an adverse effect on the surface quality of the steel. Therefore, the upper limit of the Si content is set to 0.60%.

[0026] The Mn content is set to 1.00-1.70%. Mn (manganese) improves the toughness and strength of steel within a certain range. Therefore, the lower limit of the Mn content is set to 1.00%. On the other hand, if the Mn content is greater than 1.70%, macrosegregation is likely to occur, resulting in a significant decrease in the toughness of the steel, and even delamination, which deteriorates the lamellar tearing resistance. Therefore, the upper limit of the Mn content is set to 1.70%.

[0027] The P content is set to ≤0.015%. P (phosphorus) is prone to cause solidification segregation, resulting in welding cracks and reduced toughness. It is a harmful element and should be reduced as much as possible. Considering the cost of P removal, P is limited to less than 0.015%.

[0028] The S content is set to ≤0.007%. S (sulfur) easily causes solidification segregation and forms MnS inclusions, which not only causes welding cracks and reduces toughness, but also causes lamellar tearing. It is a harmful element and should be reduced as much as possible. Considering the cost of S removal, the S content is limited to less than 0.007%.

[0029] The Nb content is set to 0.01-0.06%. Nb (niobium) is the main element for the formation of second-phase particles. The formed second-phase particles hinder the occurrence of austenite recrystallization and the growth of austenite grains through the pinning effect, so as to achieve the effect of refining austenite grains. Therefore, the lower limit of the Nb content is set to 0.01%; on the other hand, if the Nb content exceeds 0.06%, cracks are prone to occur in the inner fillet of the continuous casting special-shaped billet, which affects the surface quality of the final product and is not conducive to cost control. Therefore, the upper limit of the Nb content is set to 0.06%.

[0030] The V content is set to 0.080-0.120%. V (vanadium) is an effective element that precipitates as carbonitrides in austenite and serves as a nucleation point for ferrite transformation to refine ferrite grains. At the same time, a large amount of carbonitride second phase particles will precipitate in ferrite, which plays a precipitation strengthening role. Therefore, the lower limit of the V content is set to 0.080%. On the other hand, if the V content is greater than 0.120%, the low-temperature toughness may be impaired due to the coarseness of the precipitates. Therefore, the upper limit of the V content is set to 0.120%.

[0031] The N content is set to 0.0040-0.0100%. N (nitrogen) is an element that forms VN or V (CN) and contributes to the fine graining and precipitation strengthening of the structure. Therefore, the lower limit of the N content is set to 0.0040%. However, if the N content is greater than 0.0100%, it will cause a decrease in low-temperature toughness, continuous casting surface cracks, and steel strain aging. Therefore, the upper limit of the N content is set to 0.0100%.

[0032] The H content is set to ≤0.0002%. H (hydrogen) is the main cause of hydrogen-induced cracking in steel and is a harmful element. If the H content of the steel exceeds the limit, it will cause hydrogen-induced fracture of the steel. Therefore, the upper limit of the H content is set to 0.0002%.

[0033] The yield strength R of the hot rolled H-beam eH ≥460MPa; tensile strength R m : 540MPa~720MPa, elongation after break A: ≥20%; -20℃ impact absorption energy KV2≥150J, -40℃ impact absorption energy KV2≥120J, thickness direction performance Z≥35%.

[0034] Heavy hot-rolled H-beam products are thick, and hydrogen in the products is difficult to diffuse and overflow, which can easily cause hydrogen-induced cracks and deteriorate product performance. Through the optimization of the process flow of heavy hot-rolled H-beams, the alloy baking process is added, and the cold stacking process of the ingot off-line and the RH / VD refining and dehydrogenation process in the traditional process are removed, the low hydrogen level of the product is ensured, so that it meets the requirements of the hot charging and hot delivery process, and the hot charging and hot delivery of the product is realized, which improves the product production efficiency, saves product energy consumption, and realizes low-carbon green production. At the same time, the removal of the RH / VD refining process avoids the reduction of the N content in the steel and gives full play to the role of the V alloy.

[0035] The production process of the invention comprises the following steps: molten iron pretreatment→alloy baking→converter smelting→LF refining→continuous casting→hot charging→heating in a heating furnace→high-pressure water descaling→coiling machine rolling→universal machine rolling→cooling bed air cooling.

[0036] The present invention gives full play to the microalloying effect of Nb / V under the composition system of low carbon equivalent CEV and low welding crack sensitivity index Pcm, optimizes the rolling procedure and rolling rhythm, ensures the rolling compression in the specific rolling temperature range of the universal section, and utilizes the effects of fine grain strengthening, solid solution strengthening and phase transformation strengthening to achieve the strengthening and toughening of heavy hot-rolled H-beam, changes the traditional universal two-stage warm rolling, and improves the production line production efficiency. Specifically, the production method of the above Q460DE grade Z-direction performance hot-rolled H-beam comprises the following steps:

[0037] (1) Hot metal pretreatment: Desulfurization treatment in the desulfurization station, control [S] ≤ 0.005%, and the slag bright surface requirement ≥ 80%. ;

[0038] (2) Alloy baking: add silicon manganese alloy, high carbon ferromanganese, ferrovanadium alloy, vanadium nitrogen alloy, ferroniobium alloy for baking, the baking time is ≥40min, and the baking temperature is 250~500℃;

[0039] (3) Converter smelting;

[0040] (4) LF refining;

[0041] (5) Continuous casting;

[0042] (6) Hot loading;

[0043] (7) Heating in a heating furnace;

[0044] (8) High-pressure water descaling;

[0045] (9) Blooming mill rolling: rolling temperature 1050~1150℃;

[0046] (10) Universal rolling: flange cumulative reduction / web cumulative reduction = 1-1.1, starting rolling temperature <1000°C, final rolling temperature <930°C, 930-960°C flange cumulative compression ratio 1.5-1.6;

[0047] Continuous casting billet size: the compression ratio of the cross-sectional area of ​​the continuous casting billet to the finished product is 2.7 to 4.7, among which the compression ratio of the average thickness of the continuous casting billet flange to the thickness of the finished product flange is 1.8 to 2.7;

[0048] The capacity of hot-rolled H-beam mill is significantly lower than that of thick plate mill. In order to reduce the load of the mill, effectively reduce the number of rolling passes and improve rolling efficiency, the continuous casting billet size should be optimized according to the product thickness.

[0049] (11) Cooling bed air cooling.

[0050] The advantages of the above steps are:

[0051] ① Adding alloy baking process and eliminating the ingot off-line stack cooling process and RH / VD refining and dehydrogenation process in the traditional process ensures the low hydrogen level of the product;

[0052] ② The product can be hot loaded and hot delivered, which improves product production efficiency, saves product energy consumption, and realizes low-carbon green production;

[0053] ③The removal of RH / VD refining process avoids the reduction of N content in steel and gives full play to the role of V alloy;

[0054] ④ Optimize the rolling procedure and rolling rhythm to ensure the rolling compression in the specific rolling temperature range of the universal section, so as to utilize the effects of fine grain strengthening, solid solution strengthening and phase transformation strengthening to achieve the strengthening and toughening of heavy hot-rolled H-shaped steel, change the traditional universal two-stage warm rolling, and improve the production efficiency of the production line.

[0055] Furthermore, in step (3), in converter smelting: all the ferrovanadium alloy and 50% to 80% of the vanadium-nitrogen alloy are added before the first 1 / 2 of the molten steel is discharged.

[0056] Furthermore, in step (4), LF refining: after the LF furnace stops heating, the composition of the molten steel is adjusted according to the designed composition, and after adding the ferroniobium alloy and the remaining 20% ​​to 50% of the vanadium-nitrogen alloy, 200L / min-400L / min of argon gas is blown in for strong stirring for 2 to 6 minutes.

[0057] Furthermore, in step (6), the hot charging temperature is 500-700°C; in step (7), the heating process of the heating furnace is: preheating section: 900-1150°C, 50-60 min, heating section: 1000-1280°C, 50-60 min, soaking section: 1220-1280°C, 25-35 min.

[0058] Furthermore, in step (1), in order to control the N content of the steel, the addition ratio of vanadium-nitrogen alloy VN and vanadium-iron alloy VFe should be controlled, and the mass ratio between vanadium-nitrogen alloy VN and vanadium-iron alloy VFe is (1-2):2.

[0059] 3. Beneficial effects

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] The present invention adopts a component system with low carbon equivalent CEV and low welding crack sensitivity index Pcm, gives full play to the micro-alloying effect of Nb / V, optimizes the rolling schedule and rolling rhythm, and utilizes the effects of fine grain strengthening, solid solution strengthening and phase transformation strengthening to achieve the strengthening and toughening of heavy hot-rolled H-shaped steel, changes the traditional universal two-stage warm rolling, and improves the production efficiency of the production line; optimizes the production process, eliminates the billet offline stack cooling process and the RH / VD refining and dehydrogenation process in the traditional process, adds an alloy baking process, ensures the low hydrogen level of the product, realizes hot charging and hot delivery of the product, improves the product production efficiency, saves product energy consumption, and realizes low-carbon green production; optimizes the rolling schedule and rolling rhythm to couple the micro-alloying effect of Nb / V, realizes the universal section continuous rolling, develops 50-120mm thick Q460DE grade heavy hot-rolled H-shaped steel, improves its weldability, and enhances its usability. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 is a process flow chart of the present invention;

[0063] Figure 2 Schematic diagram of sampling position of H-beam of the present invention;

[0064] Figure 3 is the microstructure of the H-beam in Example 1;

[0065] Figure 4 is the microstructure of the H-beam in Example 3;

[0066] Figure 5 is the microstructure of the H-beam in Example 5;

[0067] Figure 6 is the microstructure of the H-beam in Comparative Example 8;

[0068] Figure 7 is the microstructure of the H-beam in Comparative Example 10;

[0069] Figure 8 This is the microstructure of the H-beam in Comparative Example 19. DETAILED DESCRIPTION

[0070] The present invention is further described below in conjunction with specific embodiments and drawings.

[0071] The Q460DE grade Z-direction performance heavy hot-rolled H-beam with excellent weldability described in Examples 1 to 6 includes the following chemical components in weight percentage: as shown in Table 1 below, the remainder not listed in Table 1 is Fe and unavoidable impurities.

[0072] Comparative Example 7-Comparative Example 21: A hot-rolled H-beam, comprising the following chemical components in weight percentage: as shown in Table 1 below, the remainder not listed in Table 1 is Fe and unavoidable impurities.

[0073] Table 1 Chemical composition (wt%) and thickness of Examples 1-6 and Comparative Examples 7-21

[0074]

[0075] A production method for fine structure of Q460DE grade Z-direction heavy hot-rolled H-beam with excellent weldability, combined with Figure 1 The process flow chart shown in the figure has the following steps:

[0076] A: Hot metal pretreatment: enter the desulfurization station for desulfurization treatment, control [S] ≤ 0.005%, and the slag bright surface requirement is ≥ 80%.

[0077] B: Alloy baking: baking time 41-43min, baking temperature 294-305℃;

[0078] C: Converter smelting: Add all vanadium-iron VFe alloy and 50% to 80% vanadium-nitrogen alloy before the 1 / 2 of molten steel is discharged.

[0079] D: LF refining: After the LF furnace stops heating, adjust the composition of the molten steel according to the designed composition, add ferroniobium alloy and the remaining 20% ​​to 50% vanadium-nitrogen alloy, and stir vigorously for 2 to 6 minutes.

[0080] In the above process, vanadium nitrogen alloy VN: vanadium iron VFe = 0.6-1; in order to control the N content of the steel, the addition ratio of vanadium nitrogen alloy VN and vanadium iron VFe should be controlled.

[0081] E: continuous casting;

[0082] F: Hot charging: Hot charging temperature 650~689℃.

[0083] G: Heating furnace heating: Heating process: preheating section 1099 ~ 1106 ℃, 55 ~ 56min, heating section 1209 ~ 1212 ℃, 52 ~ 54min, equalizing end 1231 ~ 1235 ℃, 30 ~ 32min.

[0084] H: high pressure water descaling;

[0085] I: Billet mill rolling process: rolling temperature 1089~1093℃;

[0086] J: Universal rolling: flange cumulative reduction / web cumulative reduction = 1.04-1.08, start rolling temperature 976-999°C, final rolling temperature 915-927°C, 930-960°C flange cumulative compression ratio 1.53-1.58.

[0087] K: Cold bed air cooling.

[0088] The main specific process parameters involved in the production process of the heavy hot-rolled H-beam with excellent weldability Q460DE grade Z-direction performance described in Examples 1 to 6 are shown in Table 2.

[0089] The production process of the hot-rolled H-beams in Comparative Examples 7 to 21 is the same as that in Examples 1 to 6, except that the process parameters are shown in Table 2.

[0090] Table 2 Production process parameters of Examples 1-6 and Comparative Examples 7-21

[0091]

[0092]

[0093] The test results of the second phase particle volume fraction, room temperature tensile strength, low temperature impact performance and thickness direction performance of the Q355MPa grade heavy hot-rolled H-beams described in Examples 1 to 6 and the hot-rolled H-beams described in Comparative Examples 7 to 21 are shown in Table 3, where the sampling position is at b / 6 in the flange width direction and t / 4 in the flange thickness direction, i.e. Figure 2 At A shown.

[0094] Table 3 Volume fraction and mechanical properties of the second phase particles of Examples 1-6 and Comparative Examples 7-21

[0095]

[0096]

[0097] It can be seen from Tables 1 to 3 above that the present invention can efficiently produce Q460DE grade series hot-rolled H-shaped steel with flange thickness of 50 mm to 120 mm, high strength, high and low temperature toughness, excellent weldability and thickness direction performance.

[0098] Figures 3 to 8 The microstructures of the H-beams in Examples 1, 3, and 5 and Comparative Examples 8, 10, and 19 are shown in the figures. From the comparison of the figures, it can be seen that the ferrite grain size in the embodiments is small, and the volume fraction of 6-12 um ferrite accounts for a large proportion of the total ferrite volume.

[0099] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A Q460DE grade Z-direction performance hot-rolled H-beam, characterized by: The carbon equivalent CEV of H-beam is 0.36-0.41%, and the welding crack sensitivity index Pcm is 0.18-0.23%; the flange thickness is 120mm, at 1 / 6 of the flange width and 1 / 4 of the flange thickness: The size of the Nb(CN) second phase particles is less than 60nm, the size of the V(CN) second phase particles is less than 30nm, and the microstructure is composed of ferrite and pearlite; wherein the volume fraction of the Nb(CN) second phase particles with a size of 20-40nm is 0.03-0.04%, and the volume fraction of the V(CN) second phase particles with a size of 5-15nm is 0.06-0.08%; the ferrite is less than 30μm and accounts for 74-78% of the volume, and the volume fraction of the 6-12μm ferrite accounts for 85% of the volume of the ferrite; In the chemical composition system of H-beam, the chemical composition and its weight percentage are: C: 0.04-0.12%; Si: 0.10-0.60%, Mn: 1.00-1.70%, P: ≤0.015%; S: ≤0.007%; Nb: 0.01-0.06%; V: 0.080-0.120%; N: 0.0040-0.0100%; H: ≤0.0002%, and the rest are Fe and unavoidable impurity elements, among which: the weight percentages w(Nb) and w(V) between Nb and V satisfy formula (a): w(Nb)+w(V)-0.079=0.050~0.070%(a).

2. A method for producing Q460DE grade Z-direction performance hot-rolled H-beam according to claim 1, characterized in that: The steps are: (1) Pretreatment of molten iron; (2) Alloy baking: add silicon manganese alloy, high carbon ferromanganese, ferrovanadium alloy, vanadium nitrogen alloy, ferroniobium alloy for baking, the baking time is ≥40min, and the baking temperature is 250~500℃; (3) Converter smelting; (4) LF refining; (5) Continuous casting; (6) Hot loading; (7) Heating in a heating furnace; (8) High-pressure water descaling; (9) Blooming mill rolling: rolling temperature 1050~1150℃; (10) Universal rolling: flange cumulative reduction / web cumulative reduction = 1-1.1, starting rolling temperature <1000°C, final rolling temperature <930°C, 930-960°C flange cumulative compression ratio 1.5-1.6; (11) Cooling bed air cooling.

3. The method for producing Q460DE grade Z-direction performance hot-rolled H-beam according to claim 2, characterized in that: In step (3), converter smelting: add all vanadium iron alloy and 50% to 80% vanadium nitrogen alloy before the molten steel is discharged in the first half.

4. The method for producing Q460DE grade Z-direction performance hot-rolled H-beam according to claim 2, characterized in that: In step (4), LF refining: after the LF furnace stops heating, the composition of the molten steel is adjusted according to the designed composition, and after adding ferroniobium alloy and the remaining 20% ​​to 50% vanadium-nitrogen alloy, argon gas is blown in at 200L / min-400L / min for strong stirring for 2 to 6 minutes.

5. The method for producing Q460DE grade Z-direction performance hot-rolled H-beam according to claim 2, characterized in that: In step (6), the hot charging temperature is 500-700°C; in step (7), the heating process of the heating furnace is: preheating section: 900-1150°C, 50-60 min, heating section: 1000-1280°C, 50-60 min, soaking section: 1220-1280°C, 25-35 min.

6. The method for producing Q460DE grade Z-direction performance hot-rolled H-beam according to claim 2, characterized in that: In step (2), the mass ratio of vanadium-nitrogen alloy to vanadium-iron alloy is (1-2):2.

Citation Information

Patent Citations

  • A low-cost, high-temperature toughness, 460MPa grade hot-rolled H-beam and its production method

    CN112410666B

  • A method for producing ultra-thick hot-rolled H-beams.

    CN112458364B

  • A high-performance, heavy-duty hot-rolled H-beam with a yield strength of 460 MPa and its production method.

    CN114369764B

  • Low-temperature-resistant hot-rolled H-shaped steel with yield strength of 460MPa and preparation method thereof

    CN112030074A

  • Low-cost 460MPa-grade hot-rolled H-shaped steel with excellent low-temperature toughness and production method thereof

    CN112410666A